HWU DRILLING PROJECT INVESTMENT ANALYSIS (CASE STUDY OF HWU DRILLING AS RIG REPLACEMENT PROJECT AT TANO FIELD, SINAMBUNG BLOCK) - Rhama Priwanza, Herfran
SINAMBUNG Block is operated by PETROGRAMA located in East Kalimantan Province, Indonesia. There are several blocks under the SINAMBUNG block, which TANO field being one such block. The development of the TANO field requires a high number of wells to maintain its production levels due to marginal reserves condition where its reservoirs are randomly distributed either laterally or vertically. The main focus of current development on the field is on the shallow section since the shallow wells will have lower costs proportional to their limited well reserves. Shallow zone reservoir targets are between 500 – 1,800 m below subsea level. Several optimizations have been done to lower the cost of the shallow wells, with the most recent breakthrough in the new type of wells architecture of Single or One Phase Wells (OPW), where 20” conductor pipe will be piled until 110m below subsea, then 8-1/2” or 9-1/2” borehole drilled from surface to the target reservoir depth as per requirement.